Collaboration with Universidad Catolica Del Maule - UiTM Shah Alam, Akademi Pengajian Bahasa (Academy of Language Studies, 2022)
APB has initiated a partnership with Universidad Catolica del Maule, a university from Chile. Through this collaborative effort, APB and UCM have successfully planned and conducted Mandarin and Spanish classes. This remarkable collaboration between APB and UCM is a significant milestone in APB's dynamic internationalisation mission. Also, it is exhilarating to see our lecturers enjoy teaching international students.